Teknovision Private Limited Internship Report - Tiwari, Shivam (ATLAS SkillTech University, 2024)
A great education when clubbed with practical experience turns out to be a path towards success. With Summer Internship being a mandate as per the guidelines provided by AICTE for students pursuing PGDM, it comes as a platform for everyone to effectively apply the theories learned in classroom into the real-world scenarios. This internship report highlights about all my experiences, roles and responsibilities and key deliverables as an intern for the activities that I have worked upon in my 3 months duration of internship under Teknovision Pvt. Ltd. I have also mentioned in brief about what the company is about, how it started, its presence, the services it offers, organizational structure, organization hierarchy and SWOT Analysis. While majority of the work was carried out with the comfort of my home throughout these 3 months of internship, there were few days when I had the opportunity to experience the work in office culture after there was ease down of certain restrictions. Interning at Teknovision was a one-of-a-kind experience that I will carry and apply in my career throughout.
Project Report on Teknovision Private Limited Internship Report (2022-24) Under the Guidance of Prof. Nikita Nadkarni
Keywords: AICTE; SWOT; SWOT Analysis